Effect of T-2 toxin-contaminated diet on common carp (Cyprinus carpio L.). Issue 60 (January 2017) - Matejova, Iveta; Faldyna, Martin; Modra, Helena; Blahova, Jana; Palikova, Miroslava; Markova, Zdenka; Franc, Ales; Vicenova, Monika; Vojtek, Libor; Bartonkova, Jana; Sehonova, Pavla; Hostovsky, Martin; et al.
Abstract: The T-2 toxin, a fungal metabolite produced by Fusarium molds, occurs in a range of agriculture products. Reduced availability of fish meal has led to increasing use of cereals as a source of protein in commercial aquaculture feeds, which has increased the potential for mycotoxin contamination. The purpose of this study was to investigate toxicity of T-2 toxin intake in common carp ( Cyprinus carpio L.) using haematological, biochemical and immunological parameters and oxidative stress indices. In a four-week feeding trial, fish were fed a commercial diet with 5.3 mg/kg T-2 toxin added. Ingestion of contaminated diet did not lead to mortality of fish, probably due to lower feed intake. On the other hand, it significantly affected haematological variables such as haematocrit, haemoglobin, red blood cell counts leading to anemia and white blood cell counts leading to leukopenia due to lymphopenia. Plasma glucose concentration and alanine amino transferase activity showed a significant increase while triglycerides concentration decreased. Activity of ceruloplasmin was significantly decreased in plasma. Further, liver glutathione S -transferase activity was significantly increased and catalase activity decreased, in parallel with a significant increase in caudal kidney catalase activity and a decrease in glutathione peroxidase activity. Finally, lipid peroxidation (detected as malondialdehyde) was significantly increased in the liver and caudal kidney. Changes in non-specific immune response and cytokine levels in head kidney indicated immune system sensitivity to T-2 toxin. Overall, the results demonstrate that this feed-borne mycotoxin is able to induce anaemia and oxidative stress and cause changes in the immune response of common carp. Highlights: The aim of the study was to investigate toxicity of T-2 toxin intake in common carp. Feeding trial led to changes in haematological and biochemical parameter. Lipid peroxidation was significantly increased in the liver and caudal kidney. Exposition to T2 led to changes in non-specific immune response. Exposition to T2 led to changes in mRNA expression for selected cytokines.